Estágio profissionalizante realizado no Académico Futebol Clube - Inês Filipa Bastos Pereira Pinto Mota (2016)
The present report aims to describe and analyze the developed activities during the professional internship, to acquire the Master Degree in Sports Management, ministered by the Sports College of the University of Porto, and held in Académico Futebol Clube, in Porto. It began with the settlement of the objectives for this internship, which encompassed three main areas: event management, musealization and administration. In order to accomplish the internship objectives, several activities and work methods were conceptualized and realized during this period. Regarding the event management area, my task consisted in games dynamization and the creation of advertising spaces to promote the merchandising and services of the Académico Futebol Clube. In the musealization area, it was requested a digital database of the Club's entire collection. For the administration area, my role consisted in the transcription of minutes, of the Club's Direction, into digital format. The impact of this internship in my life was very positive, both on social and communication level, due to the contacts established, not only with the Club members, but also with the public. The fulfillment of this internship allowed me to acquire greater responsibility and work methods, new skills in different areas, professional experience in my academic area, as well as develop my ability to create work systems and to adapt to unknown realities.